Dielectric relaxation in dipolar fluids. Generalized mode approach - Omelyan, I.P.; Mryglod, I.M.; Tokarchuk, M.V. (Condensed Matter Physics, 1998)
The concept of generalized collective modes, recently proposed for the investigation of simple fluids, is now applied to describe processes of dielectric relaxation in dipolar systems. The approach presented here is an extension of the dipole-density formalism to arbitrary numbers of dynamical variables and values of wavelengths. Generalized dipolar mode spectra of a Stockmayer fluid are evaluated over a wide scale of wavelengths up to the five-variable approximation. The wavevector- and frequency-dependent dielectric permittivity and dipole-moment time autocorrelation functions are calculated on the basis of analytical expressions using the dipolar modes. The obtained results are compared with those achieved in lower-order approximations and with molecular dynamics data. It is shown that the fivevariable description quantitatively reproduces the entire frequency dependence of the dielectric constant at arbitrary wavenumbers.